ВЛИЯНИЕ МЕЖОБМОТОЧНОЙ ЕМКОСТИ НА ТОЧНОСТЬ РАБОТЫ ВЫСОКОВОЛЬТНОГО ТРАНСФОРМАТОРА ТОКА - Варский , Г.М. (Інститут електродинаміки НАН України, Київ, 2014)
The processes proceeding in the secondary circuit of the high-potential current transformer under the influence of a primary current and primary voltage with the account interwinding capacitance of the transformer are investigated. Expressions for a finding of a error of the current transformer are gained at different meanings of a primary current and different phasor power factor of a highvoltage line. References 3, figures 3.